Consumer preference and the technological, cooking and nutritional quality of carioca beans - Ribeiro, Nerinéia Dalfollo; Casagrande, Cleiton Renato; Mezzomo, Henrique Caletti; Kläsener, Greice Rosana; Steckling, Skarlet De Marco (Semina: Ciências Agrárias, 2019)
Carioca beans will achieve better consumer acceptability if they exhibit high grain quality. The objectives of this work were to identify the visual quality traits that determine consumer choice of carioca beans; to evaluate whether the commercial brands of carioca beans present differences in their technological, cooking and nutritional quality traits; and to select the best commercial brand of carioca beans according to these traits using a selection index. For this purpose, six different commercial brands of carioca beans were evaluated with respect to consumer preference and their grain physicochemical traits. The visual quality traits, colour and grain size, defined the consumer choice of carioca beans. The commercial brands of carioca beans presented differences regarding their technological, cooking and nutritional quality traits. Brand 4 had lighter colour grains (L* = 53.33), a slightly red shade (a* = 6.20), medium-sized beans (27.52 g), an elliptical shape, a semi-full flatness, and a fast cooking time (15 min and 25 s). The brand 4 showed high concentrations of protein, potassium, phosphorus, calcium, zinc and copper, and this sample was the preference of 51.92% of the survey participants. The best commercial brand of carioca beans selected by the selection index was brand 4 for its technological, cooking and nutritional quality traits.